Application of Bennett mechanisms to long-span shelters - Melin, N; N. Melin (2004)
Rapidly assembled tent structures are temporary enclosures used to house people or goods. Their uses vary to include recreation, refugee housing, and military shelters. The structural concepts applied in these shelters are as variable as their uses. Some make use of a tensioned fabric and pole system to provide structural strength. Others have a load-bearing frame with attached fabric skin. Further variants make use of inflatable arches or consist of modular containers. Analysis of a number of different types of rapidly assembled tent structures reveals an area where innovation can occur. Conflicts in the last ten years suggest that rapidly assembled shelters for both military purposes and humanitarian relief have the greatest need for innovative solutions. Existing shelters used by the military lack the versatility and speed of deployment necessary in modern conflict. The lack of scalability in the designs makes it difficult to use an existing tent in different situations. They are slow to construct, heavy, and difficult to transport in large numbers. These problems suggest that there is a need for new shelters that better meet the needs of the military. The application of deployable structures technology meets military's needs for structures with the advantages of a small compacted volume, rapid assembly, and ease of deployment. This makes them ideal for application to shelter structures. The aim of this dissertation was to develop a new type of deployable, long-span shelter frame based upon tiled Bennett mechanisms. An overlapping combination of equilateral Bennett mechanisms yields a structure that opens into a half-cylinder shape, providing an enclosed space useful and applicable to the problem of deployable shelters. The specific application considered in the design portion of this process will be a long-span deployable shelter capable of housing military helicopters. This report details the development of the Bennett Shelter concept. Its deployed and compacted geometries are explored, and a procedure for determining structural properties and dimensions is presented. The full concept for the structure, from outer covering to foundation support is then detailed. Loads affecting the structure are determined, and the process of modelling and analysing the structure is then considered. Optimisation of the structure with respect to weight and serviceability requirements is conducted using a number of different materials, and full analysis of the optimal geometries is completed. As no method exists for evaluating the effect of imperfections on the deployment of overconstrained mechanisms, a procedure is derived. The effects of manufacturing imperfections on deployment of the Bennett mechanism are then explored using the method. A full examination of the variation of energy within the Bennett Shelter during deployment provides valuable insight into the performance of the structure. With the above analysis complete, it is shown that the Bennett Shelter is viable as a long-span deployable shelter.